Numerical Analysis of the Trapping Effect of Grooves with Various Cross-Sectional Shapes and Reynolds Numbers - Sung-Ho Hong (Lubricants)
This study searches for an effective cross-sectional shape of grooves by evaluating their trapping effect using numerical methods. Grooves are widely employed to enhance lubrication performance across various systems, including in bearings and valves, where they serve multiple functions, such as improving load-carrying capacity, addressing pressure imbalances, storing lubricant, and minimizing leakage. Beyond these roles, grooves are crucial in preventing three-body abrasive wear by capturing solid particles, such as wear debris, within the system. This study specifically focuses on the trapping effect of grooves, examining how variations in their cross-sectional shape and the Reynolds number of the lubricant used influence this effect. To evaluate the groove’s trapping capability, the study analyzed particle trajectories and streamlines within the groove, as well as the number of particles effectively trapped. The results indicate that grooves with certain cross-sectional shapes, particularly those generating multiple vortices and small eddy currents, demonstrate superior trapping effectiveness. These findings contribute to the design of more efficient grooves in lubrication systems, providing insights into how groove geometry can be optimized to enhance the performance and longevity of mechanical components by mitigating wear through effective particle entrapment. This research has potential applications in the design and improvement of lubrication systems where managing wear and enhancing efficiency are critical concerns.